2016
DOI: 10.1071/an14781
|View full text |Cite
|
Sign up to set email alerts
|

Reducing calcium and phosphorus in crossbred beef cattle diets: impacts on productive performance during the growing and finishing phase

Abstract: Forty 3/4 Bos indicus · 1/4 Bos taurus bulls (initial bodyweight = 214 AE 4 kg; 11 AE 0.2 months) were used in the study. Four bulls were slaughtered as reference and the other 36 bulls were allowed ad libitum consumption of treatment diets following a completely randomised 3 · 3 factorial design. The design included three diet concentrations of calcium (Ca) and phosphorus (P): standard, 50% of standard, and 75% of standard and three periods of feedlot confinement: 8, 16, and 24 weeks with four bulls per treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
6
0
4
Order By: Relevance
“…Costa e Silva et al (2015b) decreased the dietary Ca requirements recommended in the BR-CORTE (2010) by 43% in Nellore steers and heifers and verified that this decrease did not influence animal performance, intake, or nutrient digestibility. Similarly, Prados et al (2015) found that decreasing the recommended dietary Ca requirements in the BR-CORTE (2010) by 38% in Holstein × Zebu bulls did not affect animal performance or mineral concentrations in the bones. These authors concluded that lowering Ca supply could decrease costs in feedlot operations and Ca excretion to the environment.…”
Section: Calciummentioning
confidence: 89%
“…Costa e Silva et al (2015b) decreased the dietary Ca requirements recommended in the BR-CORTE (2010) by 43% in Nellore steers and heifers and verified that this decrease did not influence animal performance, intake, or nutrient digestibility. Similarly, Prados et al (2015) found that decreasing the recommended dietary Ca requirements in the BR-CORTE (2010) by 38% in Holstein × Zebu bulls did not affect animal performance or mineral concentrations in the bones. These authors concluded that lowering Ca supply could decrease costs in feedlot operations and Ca excretion to the environment.…”
Section: Calciummentioning
confidence: 89%
“…As exigências líquidas de P para ganho (ExLiGP) são apresentadas na Tabela 10.9, e o PCVZ em que não há mais acréscimo significativo de P também foi estimado. Tabela 10.9 -Exigências líquidas de P para ganho e plateau de deposição de P em função do grupo genético (zebuínos e cruzados) Recentes publicações têm abordado a necessidade de redução do impacto ambiental causado pelo excesso de P excretado por bovinos (Vasconcelos et al, 2007; Costa e Silva et al, 2015b;Prados et al, 2015). Costa e Silva et al (2015b) verificaram que a redução de 20% de P na dieta de bezerros Nelore não impactou no consumo e na digestibilidade dos nutrientes bem como no desempenho dos animais; enquanto que Prados et al (2015) avaliaram que a redução de 14% das exigências de P a partir daquela preconizada pelo BR-CORTE (2010) na dieta de bovinos cruzados não afetou o desempenho e a concentração de P nos ossos.…”
Section: Cálciounclassified
“…Tabela 10.9 -Exigências líquidas de P para ganho e plateau de deposição de P em função do grupo genético (zebuínos e cruzados) Recentes publicações têm abordado a necessidade de redução do impacto ambiental causado pelo excesso de P excretado por bovinos (Vasconcelos et al, 2007; Costa e Silva et al, 2015b;Prados et al, 2015). Costa e Silva et al (2015b) verificaram que a redução de 20% de P na dieta de bezerros Nelore não impactou no consumo e na digestibilidade dos nutrientes bem como no desempenho dos animais; enquanto que Prados et al (2015) avaliaram que a redução de 14% das exigências de P a partir daquela preconizada pelo BR-CORTE (2010) na dieta de bovinos cruzados não afetou o desempenho e a concentração de P nos ossos. Neste contexto, Erickson et al (1999;2002) não observaram diferenças no desempenho de novilhos alimentados com 71 ou 162% das exigências de P preconizadas pelo NRC (2000) ou bezerros alimentados com 76 e 190% das exigências de P preconizadas pelo mesmo sistema.…”
Section: Cálciounclassified
“…Some researchers (Esser et al 2009; Prados et al 2016; Zanetti et al 2017) have demonstrated that animals fed typical feedlot diets can meet their mineral requirements exclusively from basal feed ingredients. This is made possible because the mineral content in feedstuffs is, in general, high (Playne et al 1978).…”
Section: Introductionmentioning
confidence: 99%